Association of Agenesis of the Dorsal Pancreas With HNF1B Heterozygote Mutation: A Case Report - Guo, Mei; Xu, Qinqin; Yu, Xuefeng; Yang, Qin; Shao, Shiying (Frontiers in Endocrinology, 2021)
Background: Agenesis of the dorsal pancreas (ADP) is a rare disease, the pathogenic mechanism of which is partially related to variants of hepatocyte nuclear factor 1B (HNF1B) gene. Case presentation: We report a case of ADP, which presented with acute ketoacidosis, hyperuricemia, and liver dysfunction. In this case, the HNF1B score was estimated as 16 and a heterozygous variant of HNF1B in exon 2 (c.513G>A-p.W171X) was identified through gene sequencing. Conclusions: A good understanding of the clinical comorbidities of ADP is essential for avoiding missed diagnosis to a great extent. Moreover, estimation of HNF1B score is recommended before genetic testing.